Alan lingers in US, extends trip - Pazzibugan, Dona Z. (2017)
Foreign Secretary Alan Peter Cayetano is in no hurry to return to the country after he has to extend his visit to the United States to a month.
Keywords: Cayetano, Alan Peter S. -- Travels